2018
DOI: 10.1093/infdis/jiy184
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Viral Interference Between Influenza A Virus and Human Respiratory Syncytial Virus in a Ferret Model of Infection

Abstract: Epidemiological studies have observed that the seasonal peak incidence of influenza virus infection is sometimes separate from the peak incidence of human respiratory syncytial virus (hRSV) infection, with the peak incidence of hRSV infection delayed. This is proposed to be due to viral interference, whereby infection with one virus prevents or delays infection with a different virus. We investigated viral interference between hRSV and 2009 pandemic influenza A(H1N1) virus (A[H1N1]pdm09) in the ferret model. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(156 citation statements)
references
References 42 publications
8
148
0
Order By: Relevance
“…Similar to our study, others have found that respiratory viruses can induce heterologous immunity, which is highly dependent upon the order and timing of viral inoculations. Infection of ferrets with the 2009 pandemic H1N1 influenza A virus (pdm09) 3 or 7 days before RSV prevented or reduced infection by RSV (76). In contrast, while RSV infection prior to pdm09 did not prevent infection or reduce virus shedding, it did reduce the severity of influenza disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, others have found that respiratory viruses can induce heterologous immunity, which is highly dependent upon the order and timing of viral inoculations. Infection of ferrets with the 2009 pandemic H1N1 influenza A virus (pdm09) 3 or 7 days before RSV prevented or reduced infection by RSV (76). In contrast, while RSV infection prior to pdm09 did not prevent infection or reduce virus shedding, it did reduce the severity of influenza disease.…”
Section: Discussionmentioning
confidence: 99%
“…A key result was that varied infection kinetics and outcomes could manifest from changing the virus dose or the intrinsic virus growth rate. Although RSV dose may not affect the interaction during IAV‐RSV coinfection, the finding is relevant for RV‐IAV coinfection . However, interference in the infection of epithelial cells is not the proposed mechanism for these viruses .…”
Section: Viral–viral Coinfection Kineticsmentioning
confidence: 90%
“…In a similar interaction, IAV infection attenuates RSV by inhibiting protein synthesis and does so with little impact on IAV titers . In contrast, pre‐infection with RSV or RV does not impact influenza virus replication but can reduce disease severity . For RV, this is due to enhanced clearance of influenza virions .…”
Section: Viral–viral Coinfection Kineticsmentioning
confidence: 99%
See 2 more Smart Citations